KESEJAHTERAAN MENTAL IBU RUMAH TANGGA DI RW 6 KELURAHAN KEDUNGDORO KECAMATAN TEGALSARI - Kristianingsih, Yustina; Astuti, Marta Sri; Setyawati, Emiliana Indah Eko; Winarni, Sri (Universitas Muhammadiyah Surabaya, 2024)
Objective: Mental health is one of the important aspects in a person's life because it has a major influence on the biological, cognitive and social emotional of the individual. Well-being is something that is sought after by individuals, including mothers. In the family, mothers as housekeepers have a dominant function in a family. Even now, mothers not only take care of domestic activities, but some mothers also help their husbands increase family income. This will have an impact on the mental well-being of housewives. Methods: This study used a descriptive design with total sampling with 40 mothers as respondents. Data collection uses the Mental Health Continuum (MHC-LF) questionnaire which has been validated and reliable.. Results: The research results showed that more than 50% (55%) of mothers had high mental well-being. Conclusion: The research results still show that housewives who have low mental well-being, so it is important to develop a program to improve the welfare of housewives by collaborating with local health centers to provide education on the importance of mental health and tips for mental well-being for housewives who still have low mental well-being.